2020
DOI: 10.1093/jxb/eraa421
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide production and signalling in algae

Abstract: Nitric Oxide (NO) was the first identified gaseous messenger and is now well established as a major ubiquitous signalling molecule. The rapid enhancement of our understanding of NO biology in embryophytes came with the partial characterization of the pathways underlying its production and with the decrypting of signalling networks mediating its effects. Notably, the identification of proteins regulated by NO through nitrosation greatly enhanced our perception of NO functions. In comparison, the role of NO in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 126 publications
2
10
0
Order By: Relevance
“…Our findings expand current knowledge on the role of NO in microbial ecology. Data from the current work and from previous studies demonstrate that NO is a signaling molecule in algae (17,43,47,56,57). We identified noa genes that likely encode NOA enzymes in E. huxleyi, one of which is up-regulated during algal death and potentially facilitates enhanced NO production (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Our findings expand current knowledge on the role of NO in microbial ecology. Data from the current work and from previous studies demonstrate that NO is a signaling molecule in algae (17,43,47,56,57). We identified noa genes that likely encode NOA enzymes in E. huxleyi, one of which is up-regulated during algal death and potentially facilitates enhanced NO production (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…This latter process could involve the interaction of NR with NO-forming nitrite reductase (NOFNiR) [ 20 ]. It was found that NO plays a role in the regulation of various biochemical and physiological processes, including stress responses [ 21 , 22 , 23 ], developmental processes (leaf expansion and root growth), and phytoalexin production [ 24 ]. Furthermore, some data suggest the influence of NO on plant cell division [ 25 ].…”
Section: Ros and Rns In Plant And Algal Cellsmentioning
confidence: 99%
“…Another possible means of NO signaling are the cyclic nucleotide GMP (cGMP)-mediated pathways. Although this has so far only been described in animal cells [ 23 ]). There are indications that cGMP is also synthesized in plant cells, and this synthesis is enhanced by NO [ 39 ].…”
Section: H 2 O 2 and No Cross-talkmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have suggested that algae from different lineages, such as chlorophytes, charophytes, red algae, or diatoms, could produce NO ( Mallick et al, 1999 , 2000 ; Sakihama et al, 2002 ; Tischner et al, 2004 ; Chung et al, 2008 ; Vardi et al, 2008 ; Chow et al, 2013 ), and a review of the relevant literature indicates that NO is involved in various functions in algae ( Kumar et al, 2015 ; Astier et al, 2021 ). Briefly, NO contributes to stress responses, particularly to abiotic ones (e.g., hypoxia, wounding, UV or visible light irradiation, chemicals, heat stress, high concentrations of salt, and metal).…”
Section: Introductionmentioning
confidence: 99%